Removal of As(III) from Aqueous Solution Using Fe(III) Loaded Pomegranate Waste - Thapa, Sheela; Pokhrel, Megh Raj (Journal of Nepal Chemical Society, 2013)
A study on As(III) removal using Fe(III) loaded pomegranate waste as an adsorbent is presented. The effects of initial metal ion concentration, contact time, adsorbent dose and pH of the solution on the removal of arsenic were investigated in a batch system. The optimum pH for As(III) adsorption using Fe(III)-loaded charred pomegranate waste [Fe-CPW] was found to be 9. The equilibrium has beenachieved in 2 hours. The maximum adsorption capacity (qmax) for the adsorption of As (III) was found tobe 50 mg/g. The experimental data fitted well with the Langmuir adsorption isotherm model. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9332 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 29-36 Uploaded date: 12/16/2013